Corn Tortilla Processing Technology and Corn Chips at Farmer Group/Farming Women in Bekiung Village Kecamatan Kuala, Kabupaten Langkat, North Sumatera - Efendi, Hidir; Fridiarty, Lelly; Jumjuma, Jumjuma (Journal of Community Research and Service, 2021)
The purpose of  PKM activity is to develop the business of corn farmers/women in Bekiung village to be an economically independent business through the processing of tortillas and corn chips, the design of a corn flattening machine, the design of an amphia machine (to make thin), training in the production of tortillas and corn chips, training in business management and packaging. Specific targets to be achieved; build a corn flattening machine in order to increase corn production, construct  an ampia machine, produce tortilla’s downstream and corn chips, manage marketing and packaging. The method used is education, production training, business management training, design and assistance. The results of the service carried out show that by providing knowledge, appropriate processing technology and business/marketing management, corn farmers/women are expected to be able to exploit the abundant agricultural products with low prices. One of the advantages of making food from corn is that the raw materials are easy to get and an added value farmers.